Assemblr Edu Learning Media Based on Augmented Reality to Improve Learning Outcomes of Grade V Elementary School Students - Zumrotun Nafi’ah; Sri Sami Asih (Postgraduate, University of Mataram, 2024)
Based on the results of observations made by researchers in class V elementary school which proves that there are problems in the learning process, the lack of types and kinds of learning media used, one of which is on the learning content of Natural and Social Sciences (IPAS) on the content of the structure of the earth's layers. The reason researchers conducted this study was to develop learning media with creative and innovative to foster higher student interest in learning. This research not only aims to develop learning media but also to determine the feasibility of the media and the effectiveness of Augmented Reality-based Assemblr Edu learning media. Research that used by researchers using the Research and Development (R&D) method, and the method used uses the ADDIE method. Then, for data collection conducted by researchers through observation, interviews, and student learning outcomes. The subjects in this study were students, teachers, and a team of experts (media experts and material experts). The use of qualitative descriptive techniques, quantitative descriptive, and also iferential statistics are techniques in analyzing data on the development of this learning media. The results obtained in this study from the media expert test 87.5%, material expert test 70.8%, teacher test 91.25%, learner test 95%, as well as the results of the pretest and postest to test the effectiveness of the media developed which has very decent results from small and large groups. The N-gain results which state that the Augmented Reality-based Assemblr Edu learning media has a decent category in the use of the learning process. So, it can be concluded that the Augmented Reality-based Assemblr Edu learning media on the material of the structure of the earth's layers is well used, effective, and feasible to use in the learning process.